Lack of detectable chemosynthesis at a sponge dominated subarctic methane seep - Sinner, Melina; Hong, Wei Li; Michel, Loïc N.; Vadakkepuliyambatta, Sunil; Knies, Jochen; Sen, Arunima (Frontiers in Earth Science, 2023)
We used high-resolution imagery within a Geographic Information System (GIS), free gas and porewater analyses and animal bulk stable isotope measurements to characterize the biotic and abiotic aspects of the newly discovered Vestbrona Carbonate Field (VCF) seep site on the Norwegian shelf (63°28'N, 6° 31'E, ∿270m water depth). Free gas was mainly composed of microbial methane. Sediment porewater sulfide concentrations were in the millimolar range and thus high enough to sustain seep chemosymbiotrophic animals. Nonetheless, the VCF completely lacked chemosymbiotrophic animals despite an abundance of methane-derived carbonate crusts which are formed by the same anaerobic processes that sustain chemosymbiotrophic animals at seeps. Furthermore, none of the sampled taxa, across various trophic guilds exhibited a detectable contribution of chemosynthetically fixed carbon to their diets based on bulk stable isotope values, suggesting a predominantly photosynthetic source of carbon to the VCF seep food web. We link the absence of chemosymbiotrophic animals to highly localized methane flow pathways, which may act as a 'shunt-bypass' of the anaerobic oxidation of methane (AOM) and by extension sulfide generation, thus leading to sediment sulfide concentrations that are highly heterogeneous over very short lateral distances, inhibiting the successful colonization of chemosymbiotrophic animals at the VCF seep. Instead, the seep hosted diverse biological communities, consisting entirely of heterotrophic benthic fauna, including long lived taxa, such as soft corals (e.g., Paragorgia arborea) and stony corals (i.e., Desmophyllum pertusum, formerly known as Lophelia pertusa). Compared to the surrounding non-seep seafloor, we measured heightened megafaunal density at the seep, which we attribute to increased habitat heterogeneity and the presence of a variety of hard substrates (i.e., methane-derived authigenic carbonates, dropstones and coral rubble), particularly since the most abundant taxa all belonged to the phylum Porifera. Compared to the surrounding non-seep seafloor, marine litter was denser within the VCF seep, which we link to the more variable local topography due to authigenic carbonates, which can rip off parts of bottom trawling nets thereby making the seep act as catchment area for marine litter.